High virulence of methicillin resistant Staphylococcus aureus ST30-SCC mec IVc- spa t019, the dominant community-associated clone in Argentina - Fernández, Silvina (2017)
Community-acquired methicillin resistant Staphylococcus aureus emerged as a worldwide health problem in the last few years. In Argentina, it is found in 70% of skin and skin structure infections in previously healthy adult patients and causes severe invasive diseases. The ST30-SCCmecIVc-spat019 clone is predominant in adult infections and has displaced the previously prevalent ST5-SCCmecIVa-spat311 clone in community settings. In the present work we compared the virulence of both clones in order to explain the displacement, and found that ST30-IVc is associated with invasive infections in adult patients from Argentina and possesses a different virulence-associated genes profile compared to ST5-IVa. A representative strain of ST30 lineage has a more aggressive behavior in animal models of infection and expresses higher level of Fibronectin binding protein A coding gene, which could enhance the bacterial invasion capacity.